HUBUNGAN ANTARA MAQĀṢID AL-SYARĪ’AH DENGAN BEBERAPA METODE PENETAPAN HUKUM (QIYĀS DAN SADD/FATH AL-ŻARĪ’AH) - Fatimah Halim (State Institute of Islamic Studies (IAIN) Palu, 2010)
This article discusses the relationship between maqāṣid al-syarī'ah with several methods of determining the law. The object of the study is limited to two models of law, namely qiyās and sadd (fath) al-żarī'ah. This problem was discussed through library research by using the comparative method. The results showed that, the method of determination of the law, either through qiyās and sadd (fatḥ) al-żari'ah have a very close relationship with maqāṣid al-syarīah. In the qiyās method, maqāṣid al-syarī'ah is an important factor in assessing the illat, whereas in the method of al-żari'ah, maqāṣid al-syarī'ah it is sadd al-żarīah or fath al-żarī'ah as a determinant factor.Kata Kunci: maqāṣid al-syarīah, qiyās, sadd al-żarī’ah, fatḥ al-żari’ah